Alcohol use as a modifiable risk factor in cardiology: A qualitative study of patient perspectives in Sweden - Paul Welfordsson; Anna-Karin Danielsson; Caroline Björck; Bartosz Grzymala-Lubanski; Kristina Hambraeus; Ida Haugen Löfman; Frieder Braunschweig; Matthias Lidin; Sara Wallhed Finn (PLoS ONE, 2025)
Background Alcohol use is an important cardiovascular risk factor and a major contributor to morbidity and mortality. Successful implementation of alcohol interventions in cardiology depends on patient acceptability. Objective To understand patient perspectives on the feasibility of implementing alcohol interventions in cardiology services. Methods Multi-site qualitative study. We conducted semi-structured interviews with a heterogenous-purposive sample of 15 adult cardiology patients with hazardous alcohol use. Participants were recruited from three geographically diverse regions in Sweden (Dalarna, Gävleborg, Stockholm) and were varied in terms of sociodemographic characteristics, cardiovascular diagnosis, risk factor profile, and level of alcohol use. We applied the Capability, Opportunity, Motivation and Behaviour (COM-B) system during coding and conducted a reflexive thematic analysis. Results We identified 56 feasibility factors: 15 related to capability, 10 to opportunity, and 31 to motivation. Four themes emerged: 1. Alcohol use as relevant to cardiology, where participants recognized cardiovascular risk factors, expressed motivation for change, and identified a need to address alcohol use sensitively; 2. Aligning interventions with expectations and goals, where participants linked acceptability of alcohol interventions to personal goals and social norms; 3. Morbidity and shifting priorities, where participants prioritized quality of life and respect for autonomy; 4. Addressing barriers to alcohol dependence treatments, where participants saw a need to improve access to care. Conclusions Findings suggest that alcohol interventions are acceptable to cardiology patients with hazardous alcohol use. Implementation strategies that prioritize quality of life, respect autonomy, and align with individual expectations and goals may be among the most acceptable. We also identified an opportunity to improve access to treatments for alcohol dependence within multidisciplinary heart teams or hospital-based addiction care services.